Antidiabetic properties of garciniacowone L, a new xanthone with an unusual 5,5,8a-trimethyloctahydro-2H-1-benzopyran moiety, and other xanthones from the twig extract of Garcinia cowa Roxb. ex Choisy - Rawiwan Charoensup; Moses Egoh Betangah; Virayu Suthiphasilp; Piyaporn Phukhatmuen; Tharakorn Maneerat; Thidarat Duangyod; Surat Laphookhieo (Journal of King Saud University: Science, 2022)
The aims of this study are to investigate chemical compounds from Garcinia cowa Roxb. ex Choisy and evaluate their antidiabetic activities, including α-glucosidase inhibitory, α-amylase inhibitory, glycation, glucose consumption, and glucose uptake. The EtOAc extract of the twigs of Garcinia cowa Roxb. ex Choisy were separated and purified by chromatographic techniques to give eight compounds (1–8). Of these, a xanthone with 5,5,8a-trimethyloctahydro-2H-1-benzopyran moiety, garciniacowone L (1), was isolated as a new compound, which was characterized by extensive spectroscopic data and high-resolution mass spectrometry. The known compounds were characterized by NMR spectroscopy techniques, and by comparisons of these data with those reported. All isolated compounds except β-mangostin (4) were evaluated for antidiabetic activities. Forbexanthone (8) exhibited good α-glucosidase inhibitory activity with an IC50 value of 85.1 ± 0.3 µM. 1-Hydroxy-7-methoxyxanthone (7) inhibited the highest glycation activity with the IC50 value of 170.3 ± 0.9 µM. From cell-based assays, mangostinone (3) showed glucose consumption and glucose uptake with the IC50 value of 18.3 ± 0.5 µM and 2.9-fold, respectively. This study revealed that some xanthones isolated from Garcinia cowa Roxb. ex Choisy might be interesting for further evaluation as a new drug candidate for diabetes mellitus.